Isolation and depression in older adults in Argentina between 2020 - 2022 - Burba, Ingrid Patricia; Leardi, Romina (SCT Proceedings in Interdisciplinary Insights and Innovations, 2024)
Introduction: Isolation and depression in the context of pandemic was something that generated controversy. The fact that from one day to the next older adults could not see their loved ones because they could not leave their homes, or nursing homes, caused the quality of life to decrease. The problem is posed: What is the relationship between isolation and depression in older adults in Argentina in the period 2020 - 2022? Material and methods: The design of the study is a literature review for which a search and evaluation of the existing literature and previous research on depression, isolation and pandemic will be carried out through the databases PubMed, Google Academic, Scielo, etc. inclusion criteria were used; adults over 65 years of age in the context of pandemic between the years 2020 and 2022. Search in English and Spanish. Results: An exhaustive bibliographic search was carried out through various academic storage sites such as PubMed, Google Academic, Cohrane library, among others. Analyzing in depth 18 articles. Conclusion: The imposition of mandatory quarantine by COVID - 19 is associated with decline in mood and quality of life. Also with the decline in care in older adults in Argentina